The Waste Management and the Environmental Campaign “KangPisMan” to Awareness of the Environmental Sustainability's Importance - ARDIANTI, Dhini; HIDAYAT, Dadang Rahmat; BAKTI, Iriana; MULYANI, Henny Sri (Journal of Environmental Management and Tourism, 2022)
KangPisMan, an acronym from Kurangi, Pisahkan, dan Manfaatkan Sampah (reduce, sort, and reutilize waste), is a movement to engage the people of Bandung city to implement the 3Rs: Reduce, Reuse, Recycle on waste management. There are several approaches for the awareness using socialization for the concerns of KangPisMan, including environmental campaigns through social media platforms. This study explores the effect of the KangPisMan social media ( i.e., Instagram) environmental campaign on its followers’ waste management attitude used the Ostergaard campaign model and focusing on two main aspects of the campaign message, content and structure. The study used a quantitative approach provided by the survey method of questionnaire. The studied population was Instagram account @kangpisman followers (6,460 accounts). A hundred sample accounts were selected based on the Slovin formula using random sampling with SmartPLS 3.0 application. Results of the questionnaire from 100 selected followers accounts showed that attractive campaign messages with good content and structure delivered by KangPisMan generated positive followers’ responses. The analysis of each factor showed that the message structure significantly affected followers’ attitude on managing their waste. These findings reveal that Instagram account used for the environmental campaign purposes (@kangpisman) need serious management efforts, clear program description, creativity, attractive image visualization, communicative and easy-to-understand messages. Besides that, the applicable waste management messages contents were considered necessary to be accepted, motivate and drive the people to act positively on managing their waste.